Exact Metaphysics as an Approach to Improve the Quality of Modern Human Social Intelligence in Utilizing Technological Media - Kamil; Nurhalima Tambunan (International Journal of Society and Law, 2024)
Exact metaphysics, as an approach that combines empirical science and the concept of spirituality, offers a new method for improving the quality of modern human social intelligence. In a world increasingly filled with complex digital and social interactions, social intelligence is becoming a key factor in achieving collective prosperity. This article reviews how exact metaphysics, as taught by Prof. Kadirun Yahya, can be used to understand, shape and improve the social intelligence of modern humans. This approach involves combining scientific principles with metaphysical dimensions to overcome social challenges and human relations in the modern era by utilizing technological media in various communications and applying ethical principles.